Financial Accounting and Reporting: Text and Cases. (Book Review). - Meyer, Philip E.; Davis, Harry Z. (The Accounting Review, 1981)
Reviews the book "Financial Accounting and Reporting: Text and Cases," by Paul R. Berney, William P. Lyons and Stanley J. Garstka.